Clinical and-laboratory characteristic of Covid-19 in children during the onset of the pandemic in the Tomsk region - Yu. A. Ermolaeva; V. E. Yun; Yu. G. Samoilova; D. A. Ponomareva; O. A. Oleynik (Журнал инфектологии)
In the world practice, there is an increase in the number of cases of new coronaviruses among children against the background of mass vaccination of adults/ Numerous reports in domestic and foreign literature allow to talk about various variants of COVID-1919 in children from mild to severe forms. The aim of the study. To study clinical and laboratory characteristic of COVID-19 in children. Patients and methods. The study carried out retrospective analysis of 285 cases of children who received Children’s Infectious Hospital. G.E. Sibirtsev» from May to December 2020 with the established diagnosis of «coronavirus infections». Among them, 154 boys (54.0%), 131 girls (46.0%). Results. The average age of children with COVID-19 – 11.7 [3,42:15,67] years. Hospitalization was carried out on 4 days [2:8] day. Patients reported: weakness (61.8%), cough (50.5%), cold (46.9%), decreased appetite (25.1%), aenosis (20.4%), headache (15.3%), sore throat (14.9%), diarrhea (10.2%). Intoxication syndrome was reported in 91.9% of patients. Fever (38.3 [37.7:39.0]) °C continued for 3 [2:6] days. Asymptomatic course of the disease was observed in 22 (8.1%) children. Pneumonia was reported on the 6th [3:9] day in 46 (16.1%) patients, objectively local change syndrome was determined only in 6 (2.6%) cases. The severity of pneumonia was considered to be average in most patients (93.5%). 3 children had acute respiratory failure (4.3%). Virus exposure lasted an average of 9 [9:11] days, with 104 (36.5%) patients having the virus for 10 or more days.Conclusion. Thus, COVID-19 in children are mostly mild and manifest as intoxication and cataract syndrome from the upper respiratory tract. The lack of specific manifestations in children with pneumonia emphasizes the need for radiation therapy when there is no effect from the treatment. The long-term persistence of SARS-CoV-2, diagnosed in one third of patients, indicates an important epidemiological role of children in the spread of COVID-19.